2021
DOI: 10.3390/coatings11040443
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Epitaxial Growth of AlN Thin Films on a Mo Electrode/Sapphire Substrate Using Reactive Sputtering

Abstract: High-crystalline aluminum nitride (AlN) thin films are essential for device applications, and epitaxial growth is a promising approach to improve their crystalline quality. However, a high substrate temperature is usually required for the epitaxial growth, which is not compatible with the complementary metal-oxide-semiconductor (CMOS) process. Furthermore, it is very difficult to obtain epitaxial AlN thin films on the deposited metal layers that are sometimes necessary for the bottom electrodes. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Although predefining the release cavity on the interposer layer provides multiple benefits for both FBAR and LWR devices, the extra layers added compared with the conventional design may influence the AlN thin film, hence affecting its performance. Typically, the quality of AlN thin film is highly correlated to the quality of the Mo bottom electrode underneath [47] and the AlN thickness [14] (thicker AlN tends to yield a lower FWHM value). Although the FWHM measured in this work is not as good as some prior arts [16] due to thinner AlN thickness, the performance (k 2 t , Q) delivered is still comparable with the state-of-the-art.…”
Section: Platform Performance Evaluationmentioning
confidence: 99%
“…Although predefining the release cavity on the interposer layer provides multiple benefits for both FBAR and LWR devices, the extra layers added compared with the conventional design may influence the AlN thin film, hence affecting its performance. Typically, the quality of AlN thin film is highly correlated to the quality of the Mo bottom electrode underneath [47] and the AlN thickness [14] (thicker AlN tends to yield a lower FWHM value). Although the FWHM measured in this work is not as good as some prior arts [16] due to thinner AlN thickness, the performance (k 2 t , Q) delivered is still comparable with the state-of-the-art.…”
Section: Platform Performance Evaluationmentioning
confidence: 99%
“…Microelectromechanical systems (MEMS) based on micromachining technology are promising for applications in various industries including electronics, energy, automotive, biomedical, aerospace, and robotics. Many types of materials have been investigated for MEMS applications, and among them, aluminum nitride (AlN) has received considerable attention owing to its versatile and unique properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. AlN is a III–V compound semiconductor with a direct wide bandgap of 6.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…In AlN-based BAW resonators and high-frequency filters, out-of-plane (110)-orientated Mo thin films are typically used as bottom electrodes because the (110) texture of the Mo films enables the growth of highly c -axis (0001) crystal orientated AlN active layers, which are required for achieving the highest piezoelectric constant and electroacoustic coupling. It was revealed that the growth of (0001)-orientated AlN on (110)-textured Mo (or vice versa ) is possible thanks to the presence of the local heteroepitaxial relationship of AlN(0001)­[21̅1̅0]||Mo(110)[1̅11] with a small lattice mismatch of 4.9% and the effective reduction of the crystallization energy. , The degree of the c -axis (0001) crystal orientation in the AlN growth crucially depends on the quality of the (110)-texturing and the surface morphology of the Mo bottom electrode. Sputtering or physical vapor deposition is the most frequently used method to deposit Mo thin films with resistivities lower than 10 –6 Ω m, which are normally required to reduce the ohmic loss . Although some reported improved (110)-textures in Mo films by adjusting the working pressure, the discharge power, and the deposition rates in magnetron sputtering, the thickness of the Mo bottom electrodes typically needs to be a few hundred nanometers (e.g., ∼200–300 nm) to achieve a high degree (110)-texture evolution. , This may pose a serious challenge for further development of the AlN-based BAW technology, as the resonance frequency of a BAW device is inversely proportional to the thickness of the AlN layer and its (top and bottom) electrodes .…”
Section: Introductionmentioning
confidence: 99%